Resting cortical PET metabolic changes in psychogenic non-epileptic seizures (PNES). Issue 10 (2nd December 2014) - Arthuis, M; Micoulaud-Franchi, J A; Bartolomei, F; McGonigal, Aileen; Guedj, E
Abstract : Background: The pathophysiology of psychogenic non-epileptic seizures (PNES) is poorly understood. Functional neuroimaging data in various functional neurological disorders increasingly support specific neurobiological dysfunction. However, to date, no studies have been reported of positron emission tomography (PET) in patients presenting with PNES. Methods: Sixteen patients being evaluated in a specialist epilepsy centre underwent PET with 2-deoxy-2-[fluorine-18]fluoro-d -glucose ( 18 FDG-PET) because of suspected intractable epileptic seizures. However, in all patients, the diagnosis was subsequently confirmed to be PNES with no coexisting epilepsy. 18 FDG-PET was also performed in 16 healthy controls. A voxel by voxel intergroup analysis was performed to look for significant differences in interictal (resting state) cerebral metabolism. In addition, metabolic connectivity was studied using voxel-wise inter-regional correlation analysis. Results: In comparison to group analysis of healthy participants, the group analysis of patients with PNES exhibited significant PET hypometabolism within the right inferior parietal and central region, and within the bilateral anterior cingulate cortex. A significant increase in metabolic correlation was found in patients with PNES, in comparison to healthy participants, between the right inferior parietal/central region and the bilateral cerebellum, and between the bilateral anterior cingulate cortex and the left parahippocampal gyrus. Conclusions: To the best of our knowledge, this is the first study describing FDG-PET alterations in patients with PNES. Although we cannot exclude that our data reflect changes due to comorbidities, they may indicate a dysfunction of neural systems in patients with PNES. Hypometabolism regions might relate to two of the pathophysiological mechanisms that may be involved in PNES, that is, emotional dysregulation (anterior cingulate hypometabolism) and dysfunctional processes underlying the consciousness of the self and the environment (right parietal hypometabolism). Trial registration number: NCT00484523.